A specialized midgut region in stingless bees (Hymenoptera: Apidae: Meliponinae) - Serrao, J. E.; daCruzLandim, C. (Inst Histol Embriol-conicet, 1996)
Ultrastructure of the anterior end of the midgut of three Neotropical stingless bees, including an obligate necrophagous species Trigona hypogea, suggests that this midgut region has no role in nutrient absorption because its lumen is reduced by a thick cuticle that lines the outer epithelium of the cardiac valve. A possible involvement of this midgut region in the production of the peritrophic membrane compounds is discussed.
Keywords: cardia; cardiac valve; midgut; peritrophic membrane; stingless bees